Prarancangan Pabrik Aluminium Fluorida dari Asam Fluosilikat dan Aluminium Hidroksida Kapasitas 50.000 Ton/Tahun - Astarini, Risma Cholifah; , Eni Budiyati, S.T, M.Eng; , Dra. Kun Harismah, Ph.D (2016)
AlF3 factory will be established to meet the needs in the country and abroad. It is based on the availability of abundant raw materials and AlF3 needs continue to increase from year to year. AlF3 factory with raw materials H2SiF6 and Al(OH)3 is planned to be established in 2020 in Gresik with a capacity of 50,000 tons/year. In the process, the reaction in the reactor CSTR (Continuous Stirred Tank Reactor) takes place in an exothermic at the solid-liquid phase with the operating conditions of 70°C and a pressure of 1 atm. End process that is crystallized and dried to form a dry crystalline solids. The raw materials needed to make AlF3 with a capacity of 6313.131 kg/hour takes H2SiF6 as much 10597.052 kg/hour and Al(OH)3 as much as 5648.175 kg/hour. While the need for water utilities as much as 665,465.574 kg/hour of steam as much as 3622.882 kg/hour, as much as 1406.256 kW of electricity, compressed air as much as 115.582 kg/hour, the diesel fuel as much as 94.106 liters/hour and propane as much as 710.338 kg/hour. The factory is planned to operate for 330 days with the number of employees 214 people. The economic analysis shows the Percent Return on Investment (ROI) of 36.6% before tax and after tax of 25.6%. Pay Out Time (POT) before tax for the year of 2.15 and 2.81 after tax during the year. Break Event Point (BEP) amounted to 48.33%, Shut Down Point (SDP) 32.22% and the Discounted Cash Flow (DCF) of 34.83%. Based on the above results and to consider several aspects such as operating conditions instrument with atmospheric pressure and low temperature, the raw material is not volatile and hygroscopic, waste does not damage the environment and location of the establishment of factories in the area of nonconflict, the plant AlF3 is profitable and feasible to set. Keyword: aluminium fluoride, aluminium hydroxide, fluosilicic acid